Gamma-oryzanol as a potential intervention for normalizing insulin secretion and pancreatic β-cell function - Mamoun Abdelwahab Mohammed Elamin Alfaki; Md Nadeem Bari; Md Rizwan Ansari; Imran Mohammad; Mohammad Anwar (Faculty of Medicine, Universitas Trisakti, 2026)
The bioactive substance gamma-oryzanol (GO), which is mostly present in rice bran oil, has attracted a lot of interest due to its possible therapeutic application in metabolic conditions like diabetes mellitus. The effects of GO on insulin secretion and pancreatic β-cell function are examined in this study. Gamma-oryzanol improves β-cell viability, lowers oxidative stress, and modifies intracellular signaling pathways linked to glucose metabolism, all of which increase insulin secretion, according to experimental and clinical evidence. Additionally, GO's anti-inflammatory and antioxidant qualities shield β-cells from dysfunction and apoptosis brought on by hyperglycemia and lipid toxicity. Relevant studies were identified through a systematic search of PubMed, ScienceDirect, and Google Scholar for articles published between 2017 and 2026 using the keyword “gamma-oryzanol”, “insulin secretion”, ‘pancreatic β-cell function”. Additionally, the substance seems to support glucose homeostasis and pancreatic function by upregulating important genes involved in insulin synthesis and secretion. All things considered, GO shows great promise as a natural agent for maintaining β-cell integrity and increasing insulin secretion, providing a novel complementary approach to managing diabetes. Gamma-oryzanol is frequently linked to anti-inflammatory, anti-cancer, anti-diabetic, and cholesterol-lowering properties. Because Orz reduces insulin activity, cholesterol metabolism, and associated chronic inflammation, its potential to treat metabolic diseases has recently been investigated. After apoptosis and increased endoplasmic reticulum (ER) stress were decreased, oral GO administration increased glucose-stimulated insulin secretion in islets from diabetic mice fed a high-fat diet. We also examined the effects of GO on low-dose streptozotocin-induced diabetic mice, which demonstrated elevated ER stress and consequent β-cell apoptosis. Furthermore, γ-oryzanol improved glucose dysmetabolism in this model by lowering the mRNA levels of genes linked to apoptotic signaling and ER stress in islets. All things considered, GO shows encouraging potential as a natural agent for enhancing insulin secretion and maintaining the integrity of β-cells, providing a new complementary strategy for controlling and preventing diabetes.